COINCIDENT FLOOD FREQUENCY ANALYSIS FOR DESIGN OF CHAO PHRAYA RIVER FLOOD CONTROL SYSTEM FOR BANGKOK - T. Tingsanchali; T. Kitpaisalsakut (International Association of Lowland Technology, 1999)
Flood levels of the Chao Phraya river at Bangkok is strongly influenced by the upstream river flood levels at Bangsai and the tide levels at the river mouth at Fort Chula. A flood control system was earlier proposed by the Asian lnstitute of Technology and the Thai• Austrian Consortium for Bangkok in 1986. However, no coincident flood frequency analysis was done. In this study, a coincident flood frequency analysis is applied to determine the significance of the flood levels at Bangsai and the tide levels at Fort Chula on the flood levels at Bangkok. Also, the change in the return period of flood overtopping the existing river dikes with and without the proposed flood control scheme is determined. It is found that the return period of flood overtopping the river dikes is 2.5 years when there is no flood control scheme and is more than 1000 years when considering the flood control scheme.